2008
DOI: 10.1289/ehp.10847
|View full text |Cite
|
Sign up to set email alerts
|

High Temperatures Enhanced Acute Mortality Effects of Ambient Particle Pollution in the “Oven” City of Wuhan, China

Abstract: BackgroundWe investigated whether the effect of air pollution on daily mortality is enhanced by high temperatures in Wuhan, China, using data from 2001 to 2004. Wuhan has been called an “oven” city because of its hot summers. Approximately 4.5 million permanent residents live in the 201-km2 core area of the city.MethodWe used a generalized additive model to analyze pollution, mortality, and covariate data. The estimates of the interaction between high temperature and air pollution were obtained from the main e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
4
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 32 publications
5
93
4
4
Order By: Relevance
“…This review also underscores the lack of data describing the effects of climate change and toxicant exposures on human health. While climate change is a global phenomenon, the existing literature has only recently started to explore contaminant interactions outside of North America and Europe (e.g., Bell et al, 2008;Qian et al, 2008). A greater understanding of the biological effects of climate change on chemical toxicity continues to be needed in other parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review also underscores the lack of data describing the effects of climate change and toxicant exposures on human health. While climate change is a global phenomenon, the existing literature has only recently started to explore contaminant interactions outside of North America and Europe (e.g., Bell et al, 2008;Qian et al, 2008). A greater understanding of the biological effects of climate change on chemical toxicity continues to be needed in other parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al (2008) found a synergistic effect of PM 10 and high temperatures on daily cardio-respiratory (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007a;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006) ▪ The elderly and individuals with pre-existing cardio-respiratory disease may be more vulnerable to these effects Altered exposure and risk ▪ Some populations may experience increases or decreases in POP exposures and health risks depending on the region and diet of exposed individuals (Bard, 1999;Gordon, 1997;McKone et al, 1996;Watkinson et al, 2003) ▪ Pesticides may impair mechanisms of temperature regulation especially during times of thermal stress Increased susceptibility to pathogens ▪ Toxicants can suppress immune function, and climate-induced shifts in disease vector range will result in novel pathogen exposure (Abadin et al, 2007;Haines et al, 2006;Lipp et al, 2002;Nagayama et al, 2007;Patz et al, 2005;Rogers and Randolph, 2000;Smialowicz et al, 2001) ▪ Immune system impairment linked to toxicants may increase human vulnerability to climate shifts in pathogens ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible exposures may sensitize individuals to allergic disease ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible mortality in Wuhan, China. The PM 10 effects were strongest on extremely high temperature days (daily average temperature 33.1°C) and weakest during normal temperature days (daily average temperature 18°C).…”
Section: Air Pollutants and Cardio-respiratory Diseasementioning
confidence: 99%
“…39 Qian et al found synergistic effects of PM 10 and high temperatures on daily nonaccidental, cardiovascular, and cardiopulmonary mortality in Wuhan, China. 40 The PM 10 effects were strongest on extremely high temperature days (daily average temperature, 33.1 C), less strong on extremely low temperature days (daily average temperature, 2.2 C), and weakest on moderate temperature days (daily average temperature, 18.0 C). 40 Concerning the chronic health effects from long-term exposure to air pollution, there were several ecological and cross-sectional studies in the 1990s.…”
Section: Short-term Exposure Studiesmentioning
confidence: 92%
“…40 The PM 10 effects were strongest on extremely high temperature days (daily average temperature, 33.1 C), less strong on extremely low temperature days (daily average temperature, 2.2 C), and weakest on moderate temperature days (daily average temperature, 18.0 C). 40 Concerning the chronic health effects from long-term exposure to air pollution, there were several ecological and cross-sectional studies in the 1990s. No cohort studies have been completed or published in China.…”
Section: Short-term Exposure Studiesmentioning
confidence: 92%
“…For example, a large number of heat-related deaths have been reported in the United States (Center for Disease Control and Prevention 1994;Curriero et al 2002;Hoshiko et al 2010), Europe (Keatinge et al 2000a;Keatinge et al 2000b;Huynen et al 2001), and Asia (Qian et al 2008;Chung et al 2009). A recent study by Berko et al examined deaths attributed to extreme weather events from 2006 to 2010 in the United States and found that each year about 2,000 U.S. residents died from weather-related causes, and among those 31% died due to exposure to excessive heat, heat stroke, and/or sun stroke (Berko et al 2014).…”
Section: Extreme Heat and Health Impactsmentioning
confidence: 99%